Religion, space and culture - Guarda, I. V. (2017)
Traditional places of worship were related with sacred spaces and this fact has been reflected in spatial cultures and within the structures of the city and territory. Dematerialization and placelessness characterizes the new urban landscape. Location and functionality of the buildings seem to be the common elements between new religious movements. The appropriation of available spaces and buildings (factories and industrial structures, warehouses, shops, cinemas, etc.) with good global accessibility seems to be the main reasons for choosing a place for worship. This paper examines the relationship between space and religion within Lisbon landscape and it aims to answer the following questions: In which way spatiality has implications in the constitution of the new places of worship? What is their relationship with the local communities and how they help to form new spatial cultures and urbanities in suburban landscapes? What are the change and persistence of the traditional pattern of sacred spaces as places of worship? To answer this questions, we present a new methodology to investigate the urban spatial structure by using Space Syntax with the GIS for analysis and visualization of places of worship. Two levels of scale analysis were required: Global (Lisbon city and suburbs) and local (neighborhood-street). Space Syntax models the spatial configurations of urban spaces by using a connectivity graph representation. Using GIS software all places of worship were mapped within the region according to different religions. The patterns of distribution and clustering were then correlated with the syntactic measures.